2017
DOI: 10.1111/apha.12853
|View full text |Cite
|
Sign up to set email alerts
|

The water channel AQP1 is expressed in human atherosclerotic vascular lesions and AQP1 deficiency augments angiotensin II‐induced atherosclerosis in mice

Abstract: AQP1 is expressed in atherosclerotic lesion neovasculature in human and mouse arteries and AQP1 deficiency augments lesion development in ANGII-promoted atherosclerosis in mice. Normal function of AQP1 affords cardiovascular protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…It is likely that this distribution of water permeability in the arterial wall will play an important role in many disease states as well as different therapeutic approaches. It has been recently reported that AQP1 plays a protective role against hypertension-augmented atherosclerosis in mice (33). This observation supports our hypothesis that AQP1 plays a role in reducing pressure-related strain on the endothelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…It is likely that this distribution of water permeability in the arterial wall will play an important role in many disease states as well as different therapeutic approaches. It has been recently reported that AQP1 plays a protective role against hypertension-augmented atherosclerosis in mice (33). This observation supports our hypothesis that AQP1 plays a role in reducing pressure-related strain on the endothelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the identification of mutations classically related to familial PAH (BMPR-2, TBX4, KCNK3) are not more frequent among patients with a PAA [1]. Furthermore, although some molecular pathways altered in PAH have been shown to be somehow implicated in great vessel aneurysm development (e.g., increased ALK1 receptor pathway activation in TAA [18], ENG mutations in some patients with hereditary hemorrhagic telangiectasia [19] and TAA or CAV1 and AQP1 implication in abdominal aorta aneurysm [20,21]), their association with PAA has not been described. However, some of the molecular pathways related to the development of TAA have been described to have a role in PAH pathogenesis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Among the orthodox AQPs, AQP1 was found to be the major water channel expressed in endothelial membranes supporting a major role in transcellular water movement throughout the body [ 12 , 13 ]. Notably, the importance of AQP1 to maintain endothelial homeostasis and cardiovascular health has been recently reported [ 14 , 15 ]. Endothelial dysfunction is a well-established response to cardiovascular risk factors that precedes atherosclerosis development.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction is a well-established response to cardiovascular risk factors that precedes atherosclerosis development. It was documented that AQP1 is expressed in human atherosclerotic lesions and its deficiency was related to endothelial dysfunction and atherosclerosis progression [ 15 ]. In another example, illustrating the importance of AQPs in health, besides a strong involvement in gastrointestinal pathophysiology [ 16 ], aquaglyceroporins are emerging as key players in adipose tissue homeostasis and insulin response with potential implications in obesity and metabolic-related complications, such as metabolic syndrome and cardiovascular disease (CVD) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%